The Minguet Quartet: with Andreas Klein, piano - Colorado State University, producers (managers); Lincoln Center (Fort Collins, Colo.), producers (managers) (Colorado State University. Libraries, 2016)
Date on poster is incorrect, 1/28/15 should be 1/28/16.
Keywords: The Minguet Quartet (Griffin Concert Hall, 2016)